Thermal Spectral and Magnetic Studies of Citral-anthranilic Acid and Citral-5-bromo-anthranilic Acid Complexes of Co(II), Ni(II) and Cu(II) - Ajitha Devi, P.; Parameswaran, Geetha (Asian Journal of Chemistry, 2010)
Citral-anthranilic acid and citral-5-bromo-anthranilic acid a novel Schiff base, form 1:1 complexes with Co(II), Ni(II) and Cu(II) acetates. All the complexes are found to be non-electrolytes in methanol and octahedral structures are assigned to them. IR studies reveal that the complexes are formed by the replacement of hydrogen atom of COOH group by the metal with the azomethine nitrogen co-ordinating to the metal. The thermal decomposition of [ML´(OAc)(H2O)3], and [ML"(OAc)(H2O)3], where M = Co, Ni, Cu, was studied by TG technique. The mechanism of the decomposition has been established from TG data. The kinetic parameters E, activation energy preexpoential factor (A) and entropy of activation (ΔS) were calculated from TG curves using mechanistic and non- mechanistic equations. On the basis of our findings the relative thermal stabilities of the chelates have been evaluated.